Filaggrin silencing by shRNA directly impairs the skin barrier function of normal human epidermal keratinocytes and then induces an immune response - Dang,N.N. (2015)
The objective of this study was to investigate whether a single defect in skin barrier function simulated by filaggrin silencing could induce Th2-predominant inflammation. Filaggrin gene expression was silenced in cultured normal human epidermal keratinocytes (NHEKs) using small hairpin RNA (shRNA, GTTGGCTCAAGCATATTATTT). The efficacy of silencing was confirmed by polymerase chain reaction (PCR) and Western blotting. Filaggrin-silenced cells (LV group), shRNA control cells (NC group), and noninfected cells (Blank group) were evaluated. The expression of cornified cell envelope-related proteins, including cytokeratin (CK)-5, -10, -14, loricrin, involucrin, and transglutaminase (TGM)-1, was detected by Western blotting. Interleukins (IL)-2, IL-4, IL-5, IL-12p70, IL-13, and interferon-gamma (IFN-γ) were detected by enzyme-linked immunosorbent assay (ELISA). After filaggrin was successfully silenced by shRNA, the expressions of CK-5, -10, -14, involucrin, and TGM-1 in NHEKs were significantly downregulated compared to the Blank and NC groups (P<0.05 or P<0.01); only loricrin expression was markedly upregulated (P<0.01). Filaggrin silencing also resulted in significant increases of IL-2, IL-4, IL-5, and IL-13 (P<0.05 or P<0.01), and significant decreases of IL-12p70 and IFN-γ (P<0.01) compared with cells in the Blank and NC groups. Filaggrin silencing impaired normal skin barrier function mainly by targeting the cornified cell envelope. The immune response after filaggrin silencing was characterized by Th2 cells, mainly because of the inhibition of IFN-γ expression. Lack of filaggrin may directly impair skin barrier function and then further induce the immune response.